2014
DOI: 10.5455/ijmsph.2014.140820141
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding exclusive breastfeeding among mothers attending primary health care centers in Abha city

Abstract: Background: Exclusive breastfeeding for 6 months is viewed as a major public health intervention to reduce the child mortality, particularly, in the neonates and infants. Aims & Objectives: To study the knowledge, attitude and practice regarding exclusive breastfeeding as well as to identify its determinants and explore barriers against it among mothers in Abha City. Materials and Methods: A cross sectional study was adopted. It included all mothers, who have a child aged 6-12 months, attending primary health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 41 publications
3
60
3
2
Order By: Relevance
“…This study shows that mothers who have good knowledge towards EBF are 69.8% which is higher than a study conducted in Abha city, Saudi Arabia, which was 55.3% [10], and Nigeria that was 31% [11] and Guba Lafto woreda, Ethiopia (65.1%) [9]. Contrary to this, the finding is lower than a study conducted in Calabar, Nigeria, which was 80% [12] and Bedele town in Ethiopia where it is was 87.3% [13].…”
Section: Discussioncontrasting
confidence: 59%
“…This study shows that mothers who have good knowledge towards EBF are 69.8% which is higher than a study conducted in Abha city, Saudi Arabia, which was 55.3% [10], and Nigeria that was 31% [11] and Guba Lafto woreda, Ethiopia (65.1%) [9]. Contrary to this, the finding is lower than a study conducted in Calabar, Nigeria, which was 80% [12] and Bedele town in Ethiopia where it is was 87.3% [13].…”
Section: Discussioncontrasting
confidence: 59%
“…10,14 In Saudi Arabia, a study reported that exclusive breastfeeding practices were suboptimal in Abha city, despite most participants demonstrating either good (55.3%) or excellent (30.7%) levels of knowledge regarding breastfeeding practices and 62.2% reporting positive attitudes towards breastfeeding; in contrast, unsatisfactory levels of knowledge were found in only 14% of mothers overall. 16 In Bahrain, exclusive and continued breastfeeding rates in 2010 among children <6 and 20-23 months old were 34% and 41%, respectively. 17 Moreover, two-thirds of Bahraini mothers supplemented breastfeeding with other forms of nutrition before their babies were six months old.…”
Section: Breastfeeding Trends In Gulf Cooperation Council Countriesmentioning
confidence: 99%
“…24 Another study among Saudi Arabian employed mothers who had undergone Caesarean deliveries and did not receive breastfeeding education noted that the main factors which doubled the risk of failing to breastfeed were work-related problems, insufficient breast milk and maternal and neonatal health problems. 16 In Oman, suboptimal breastfeeding practices have reportedly been linked to a lack of continuity of support, inadequate healthcare staff training/education and increased marketing of infant formula. 18,25 Fortunately, in order to revitalise the BFHI campaign, Oman has recently adopted the WHO international guidelines for the marketing of breast milk substitutes.…”
Section: Determinants Of Breastfeeding Practices In Gulf Cooperation mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Our study provides a valuable culture-specific insight into the determinants of BF intentions and infant feeding choices. There have been several efforts to investigate these factors among young mothers and college students around the globe, including Kuwait, 15 Yemen, 16 Saudi Arabia, [17][18][19] Jordan, 20 Lebanon and Syria, 21 the USA, 13 Hong Kong 22 and China. 23 To the best of the authors' knowledge, ours is the first study to assess the relationship between BF knowledge and attitudes using validated scales in a sample of Kuwaiti college students, faculty and staff.…”
Section: Introductionmentioning
confidence: 99%